2021
DOI: 10.1108/jhr-09-2020-0414
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related online misinformation in Bangladesh

Abstract: PurposeThis paper aims to understand the popular themes of coronavirus disease 2019 (COVID-19)-related online misinformation in Bangladesh and to provide some suggestions to abate the problem.Design/methodology/approachThis paper discusses online COVID-19-related misinformation in Bangladesh. Following thematic analyses, the paper discusses some dominant misinformation themes based on the data collected from three fact-checking websites of Bangladesh run by media professionals and scholars.FindingsCOVID-19-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Third, analysis with a larger dataset or more cases of misinformation might produce different results. Also, unlike the present study, most of the previous studies on COVID-19 misinformation dealt with misinformation claims and contents ( Al-Zaman, 2021b ; Brennen et al., 2020 ; Sutaria, 2020 ). Finally, this study is unable to collect and analyze the sociodemographic information of the users because (a) Facebook's account privacy often do not let such information publicly available, (b) collecting such data is time-consuming, and (c) accessing such data either manually or via API (Application Programming Interface) can potentially violate the users' right to privacy.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Third, analysis with a larger dataset or more cases of misinformation might produce different results. Also, unlike the present study, most of the previous studies on COVID-19 misinformation dealt with misinformation claims and contents ( Al-Zaman, 2021b ; Brennen et al., 2020 ; Sutaria, 2020 ). Finally, this study is unable to collect and analyze the sociodemographic information of the users because (a) Facebook's account privacy often do not let such information publicly available, (b) collecting such data is time-consuming, and (c) accessing such data either manually or via API (Application Programming Interface) can potentially violate the users' right to privacy.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, before selecting any misinformation, we checked the availability of that misinformation on Facebook through searching. Following the five most popular themes of misinformation (i.e., health, religion, politics, crime, and entertainment) ( Al-Zaman, 2021b ), we finally selected five popular and available misinformation listed on the fact-checking website: one misinformation from each theme. A few previous studies also identified popular misinformation themes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bangladesh, from the very beginning of the pandemic, a substantial amount of unawareness, rumors, and misinformation among general people about COVID-19 have been reported [ 14 ]. It is also expected that there might be considerable misinformation and hesitancy in taking COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing number of Internet users and the spread of online misinformation about vaccines, which has become a global phenomenon, is recognized as a major threat. This problem is particularly widespread in countries in which communication is less efficient and reliable information flow is not ensured (Al-Zaman, 2020). The World Health Organization has announced that the rejection of vaccines and hesitation in getting them are the main threats to global health.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%